Method for enabling ferroelectric ceramic material to have large displacement and shape memory effect

By preparing electrodes on the upper and lower surfaces of ferroelectric ceramic sheets and performing multiple periodic polarization of positive and reverse electric field, the problem of insufficient performance of lead-free ferroelectric ceramic materials is solved, and the large displacement and shape memory effect are improved, which significantly improves the application performance of lead-free ferroelectric ceramics.

CN119866168APending Publication Date: 2025-04-22SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311362682.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The performance of existing lead-free ferroelectric ceramic materials is far less than that of lead-based ferroelectric ceramics, and the deformation of a single ceramic material is very small, making it difficult to meet the needs of actual engineering applications.

Method used

After the electrodes were prepared on the upper and lower surfaces of the ferroelectric ceramic sheet, multiple periodic polarization treatments were performed to form surface layers with different physicochemical properties, enhancing the displacement output and shape memory effect of the ferroelectric ceramic.

Benefits of technology

Through this method, the apparent strain of ferroelectric ceramic materials can reach ~5%, and even reach 11% under high temperature conditions, which significantly improves the displacement output performance of lead-free ferroelectric ceramics, reduces the use of lead-based ferroelectric ceramics, and even achieves lead-freeization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866168A_ABST
    Figure CN119866168A_ABST
Patent Text Reader

Abstract

The invention relates to a method for enabling a ferroelectric ceramic material to have large displacement and a shape memory effect, which comprises the following steps: preparing an electrode on the upper / lower surface of a ferroelectric ceramic sheet, and then carrying out periodic polarization treatment on positive and negative electric fields for multiple times, so as to improve the displacement and the shape memory effect; and the thickness of the ferroelectric ceramic sheet is less than or equal to 0.2 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for making a ferroelectric ceramic material have large displacement and shape memory effects, and belongs to the technical field of processing ferroelectric ceramic materials. Background Art

[0002] Ferroelectric ceramics have become the core driving components of devices such as microfluidic pumps, atomic force microscopes, and ultrasonic scalpels because they can achieve efficient conversion between electrical energy and mechanical energy. Therefore, the development of ferroelectric ceramics with large deformation is crucial for the upgrading of the above-mentioned electromechanical coupling applications. It is generally believed that the macroscopic strain of ferroelectric materials mainly comes from the contribution of intrinsic strain (electrostriction and piezoelectric response) and extrinsic strain (ferroelectric domain inversion and phase structure transformation). In the past few decades, researchers have generally adopted methods such as element doping and quasi-isotropic phase boundary design to improve the intrinsic strain output characteristics of ceramic samples, and have achieved great success in lead-based ferroelectric materials (lead zirconate-lead titanate solid solution system, lead magnesium niobate-lead titanate solid solution system).

[0003] However, the lead element in lead-containing ferroelectric ceramics will volatilize violently during the sintering process, which will not only cause environmental pollution, but also endanger human health. Therefore, countries such as the European Union, Japan and China have successively formulated restrictions on lead-containing electronic components. However, the performance of lead-free ferroelectric ceramic materials is far inferior to that of lead-based ferroelectric ceramics, and there is still a long way to go before practical engineering applications. In addition, the deformation of a single ceramic material is very small, and its electro-induced strain is generally only about 0.1%. In actual applications, it is often necessary to increase the displacement output by stacking multiple layers, or to design a mechanical structure that amplifies micro-displacement, which undoubtedly increases the complexity and cost of the drive system. Moreover, once the electric field is removed, the ferroelectric ceramic will return to the initial strain state, which is very energy-consuming for some applications that require continuous strain output. Summary of the invention

[0004] In view of the shortcomings of the above-mentioned existing performance optimization methods, the purpose of the present invention is to provide a method for making ferroelectric ceramic materials have large displacement and shape memory effects, comprising: after preparing electrodes on the upper / lower surface of the ferroelectric ceramic sheet, it is subjected to multiple positive and negative electric field periodic polarization treatments, thereby achieving the improvement of displacement and shape memory effects; the thickness of the ferroelectric ceramic sheet is ≤0.2mm.

[0005] In the present invention, periodic polarization forms a surface layer in the ferroelectric ceramic sample whose physical and chemical properties are different from those in the bulk. Under the action of the electric field, the spontaneous polarization near the surface layer tends to undergo non-180° reversal, and non-180° reversal often causes the ferroelectric ceramic sample to produce a huge displacement output and shape memory effect.

[0006] Preferably, the material of the ferroelectric ceramic sheet includes one of sodium bismuth titanate-based ferroelectric ceramics, sodium potassium niobate-based ferroelectric ceramics, sodium bismuth titanate-barium titanate solid solution system ferroelectric ceramics, bismuth ferrite-barium titanate solid solution system ferroelectric ceramics, bismuth tungstate ferroelectric ceramics and bismuth calcium niobate ferroelectric ceramics.

[0007] Preferably, the method for thinning the ferroelectric ceramic sheet comprises: When the thickness of the ferroelectric ceramic sample is greater than 0.5 mm, use 200-500 mesh sandpaper for thinning; When the thickness of the ferroelectric ceramic sample is ≤0.5 mm, use 500-2000 mesh sandpaper for thinning.

[0008] Preferably, the electrode is a precious metal electrode, preferably a gold electrode, a platinum electrode or a silver electrode; the preparation method of the precious metal electrode comprises: applying the precious metal slurry on the upper and lower surfaces of the ferroelectric ceramic sheet, and then drying or sintering to obtain the precious metal electrode; preferably, the sintering temperature is 550-850°C, and the time is 10-30 minutes.

[0009] Preferably, the electric field intensity of the multiple positive and negative electric field periodic poling treatments is greater than the coercive field of the ferroelectric ceramic sheet, preferably 1.2 to 2.2 times the coercive field of the ferroelectric ceramic sheet, more preferably 1.2 to 1.6 times the coercive field of the ferroelectric ceramic sheet, and most preferably 1.4 to 1.6 times the coercive field of the ferroelectric ceramic sheet; The frequency of the multiple positive and negative electric field periodic polarization treatments is 0.1 to 20 Hz; The number of cycles of the multiple positive and negative electric field periodic polarization treatments is at least 20.

[0010] Preferably, the thickness of the ferroelectric ceramic sheet is 0.05-0.2 mm, preferably 0.1 mm.

[0011] In another aspect, the present invention provides a ferroelectric ceramic sheet prepared by the above method.

[0012] Beneficial effects of the present invention: The method of the present invention is simple and has a wide range of applications, and is applicable to a variety of different systems of ferroelectric ceramics, including but not limited to: sodium bismuth titanate [(Bi 0.5 Na 0.5 )TiO3] based, potassium sodium niobate [(K 0.5 Na 0.5 )NbO3] based, sodium bismuth titanate-barium titanate [(Bi 0.5 Na 0.5 )TiO3-BaTiO3] solid solution system, bismuth ferrite-barium titanate [BiFeO3-BaTiO3] solid solution system, bismuth tungstate (Bi2WO6) and calcium bismuth niobate (CaBi2Nb2O9) ferroelectric ceramics; The present invention can make 0.937 (Bi 0.5 Na 0.5 )The apparent strain of TiO3-0.063BaTiO3 reaches ~5%, and the apparent strain under high temperature conditions can even reach 11%; The present invention improves the displacement output performance of lead-containing / lead-free ferroelectric ceramics, can reduce the usage of lead-based ferroelectric ceramics, and even achieve lead-free, thus having great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 For different thicknesses of 0.937 (Bi in Example 1 0.5 Na 0.5 )Hysteresis loop and nominal strain curve of TiO3-0.063BaTiO3 ceramics under 84kV / cm electric field; Figure 2 The rectangular 0.937 (Bi 0.5 Na 0.5 )Deformation photo of TiO3-0.063BaTiO3 ceramic sheet after being polarized in a positive electric field; Figure 3 The rectangular 0.937 (Bi 0.5 Na 0.5 )Deformation photo of TiO3-0.063BaTiO3 ceramic sheet after being polarized in a negative electric field; Figure 4 The rectangular 0.937 (Bi 0.5 Na 0.5 )Deformation photo of TiO3-0.063BaTiO3 ceramic sheet after being polarized by AC electric field; Figure 5 For Example 3 (Bi 0.5 Na 0.5 )TiO3, (K 0.5 Na 0.5 )O3, 0.7BiFeO3-0.3BaTiO3 and CaBi2Nb2O9 ferroelectric ceramics with a thickness of 0.12 mm. DETAILED DESCRIPTION

[0014] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0015] In the present disclosure, the method of thinning the thickness and plating electrodes on the sample surface is used to induce non-uniform deformation of the ferroelectric ceramic material, so that the ferroelectric ceramic produces a large displacement output and a significant shape memory effect.

[0016] Thinning of thick ferroelectric ceramic slices. Ceramic slices of different thicknesses (h) are obtained by mechanical grinding and polishing, wherein: 0.05mm≤h≤0.5mm. Specifically, the ferroelectric ceramic is fixed on a sample carrier, and sandpaper of corresponding mesh is selected according to the thickness and hardness of the ceramic for alternating double-sided grinding and thinning. When the sample thickness is greater than 0.5mm, use 200-500 mesh sandpaper for rapid thinning. When the sample thickness is less than or equal to 0.5mm, use 500-2000 mesh sandpaper for slow thinning until the ideal thickness is reached. Preferably, the ideal thickness is 0.2mm or less, and the effect and performance are best when the thickness reaches about 0.1mm.

[0017] Conductive silver paste is applied to the upper and lower surfaces of the ferroelectric ceramic sheet to form an electrode layer. As an example, the thinned ceramic sheet is cleaned with alcohol or acetone, and then the conductive paste is evenly applied to the upper and lower surfaces, and finally dried and sintered to make the electrode material closely adhere to the surface of the ceramic sheet. Among them, the conductive paste is silver paste, platinum paste or gold paste, among which silver paste has the best effect.

[0018] Ferroelectric ceramic materials with both electro-bending deformation effect and shape memory effect can be obtained through AC electric field treatment. By connecting the electrodes of the ceramic sheet to a high-voltage AC power supply and performing multiple positive and negative electric field polarization treatments, ferroelectric ceramic materials that can generate large displacement output under the action of the electric field and have shape memory effect can be obtained. Among them, the electric field intensity of the periodic polarization treatment should be greater than the coercive field of the ceramic material, and the number of cycles should be more than 20 times.

[0019] The ferroelectric ceramic material prepared by the method of the present invention can significantly enhance the surface effect of the ceramic material, and the apparent strain value measured by a commercial ferroelectric analyzer (TF Analyzer 2000E; aixACCT, Aachen, Germany) can reach more than 1%.

[0020] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0021] Example 1: 0.937 (Bi prepared by conventional solid phase reaction method 0.5 Na 0.5 )TiO3-0.063BaTiO3 ferroelectric ceramics (coercive field is about 41kV / cm) are used as research objects, the thickness of the ceramic is 1.5mm and the diameter is 8.7mm: Step 1: First, use the heating platform to make the surface of the alumina sample carrier reach the temperature that melts the paraffin, and then evenly apply the paraffin on the surface of the sample block where the sample will be fixed. After the sample block cools down, the ceramic sample will be fixed on the sample block. First, use a metallographic sample grinding and polishing machine with 500-grit sandpaper to thin the ceramic sample to a grinding depth of 0.3mm; then heat the sample block to separate the ceramic sample from the sample block, flip the sample, and continue to thin it after cooling, with a grinding depth of 0.3mm; alternate grinding in this way to thin the ceramic thickness to about 0.5mm; Step 2: Select 1000-grit sandpaper and use a metallographic sample grinding and polishing machine to continue grinding the piezoelectric ceramics, so that the thickness of the ceramic samples reaches 0.5 mm (sample 1), 0.3 mm (sample 2), 0.2 mm (sample 3) and 0.1 mm (sample 4) respectively; Step 3: Soak the polished thin slice sample in acetone to remove stains and paraffin on the sample surface. Then coat the upper and lower surfaces of the sample with room temperature silver paste and dry it in an oven at 80°C. Then, the ferroelectric and strain properties can be tested using a commercial ferroelectric analyzer (TFAnalyzer2000E; aixACCT, Aachen, Germany).

[0022] A 0.5 mm thick ceramic sample 1 was placed in the sample chamber of a ferroelectric analyzer. The test voltage frequency was 1 Hz. The test voltage amplitude started from 100 V and gradually increased by 50 V to 4200 V. Then, the test was repeated 20 times at the highest voltage of 4200 V (2.04 times the coercive field) to obtain stable performance. 0.5 Na 0.5 )The hysteresis loop and strain electric field curve of TiO3-0.063BaTiO3 ferroelectric ceramics are shown in Figure 1 As shown in a, the residual polarization P r =36.14μC / cm 2 , the maximum electrostrain output is about 0.18%.

[0023] The 0.3 mm thick ceramic sample 2 was placed in the sample chamber of the ferroelectric analyzer. The test voltage frequency was 1 Hz. The test voltage amplitude started from 100 V and gradually increased by 50 V to 2520 V. Then, the test was performed 20 times under the condition of the highest voltage of 2520 V (1.97 times the coercive field) to obtain stable performance.0.5 Na 0.5 )The hysteresis loop and strain electric field curve of TiO3-0.063BaTiO3 ferroelectric ceramics are shown in Figure 1 As shown in b, the residual polarization P r Compared with the 0.5 mm thick sample, it is reduced to 34.93 μC / cm 2 , the maximum electrostrain output is about 0.34%.

[0024] The 0.2 mm thick ceramic sample 3 was placed in the sample chamber of the ferroelectric analyzer. The test voltage frequency was 1 Hz. The test voltage amplitude started from 100 V and gradually increased by 50 V to 1680 V. Then, the test was performed 20 times at the highest voltage of 1680 V (1.79 times the coercive field) to obtain stable performance. 0.5 Na 0.5 )The hysteresis loop and strain electric field curve of TiO3-0.063BaTiO3 ferroelectric ceramics are shown in Figure 1 As shown in c, the remanent polarization Pr = 33.14μC / cm 2 , the maximum electrostrain output increases to ~1.02%.

[0025] Finally, the 0.1 mm thick ceramic sample 4 was placed in the sample chamber of the ferroelectric analyzer. The test voltage frequency was 1 Hz, and the test voltage amplitude was gradually increased from 100 V to 840 V at 50 V intervals. Then, the test was performed 20 times at the highest voltage of 840 V (2.04 times the coercive field) to obtain stable performance. 0.5 Na 0.5 )The hysteresis loop and strain electric field curve of TiO3-0.063BaTiO3 ferroelectric ceramics are shown in Figure 1 As shown in (d), the remnant polarization is significantly reduced to 27.46 μC / cm 2 , the maximum electrostrain output increases sharply to ~5.51%. The 0.1mm thick ceramic sample not only has a very large apparent strain, but also has a much higher displacement output than the 0.5mm thick ceramic sample under the same electric field conditions.

[0026] Example 2: Selecting a rectangular 0.937 (Bi 0.5 Na 0.5 )TiO3-0.063BaTiO3 ferroelectric ceramics (coercive field of 43.48 kV / cm) were used as the research object. The ceramic thickness was 2.5 mm, the length was 23 mm, and the width was 4.3 mm: Step 1: First, use the heating platform to make the surface of the alumina sample block reach the temperature that melts the paraffin, then evenly apply the paraffin on the surface of the sample block where the sample will be fixed. After the sample block cools down, the ceramic sample will be fixed on the sample block. First, use a metallographic sample grinding and polishing machine with 500-grit sandpaper to thin the ceramic sample to a grinding depth of 0.3mm; then heat the sample block to separate the ceramic sample from the sample block, flip the sample, and continue to thin it after cooling, with a grinding depth of 0.3mm; alternate grinding in this way to thin the ceramic thickness to about 0.5mm; Step 2: Select 1000-grit sandpaper and use a metallographic sample grinding and polishing machine to continue grinding the piezoelectric ceramics until the thickness of the ceramic sample reaches about 0.125 mm; Step 3: Soak the polished thin slice sample in acetone to remove stains and paraffin on the sample surface. Then apply room temperature silver paste on the upper and lower surfaces of the sample and place it in an 80°C oven to dry. Step 4: Fix one end of the electrode-coated ceramic sheet with a clamp and connect a high-voltage power supply to drive the ceramic to deform.

[0027] When the electrodes of the ceramic sheet are connected to a high voltage power supply and activated for 100 seconds under the action of a triangular wave electric field with an amplitude of 700V (1.29 times the coercive field) and a frequency of 1Hz. Figure 2-4 As shown, when an electric field of 60 kV / cm is applied to the upper surface of the sample, the long ceramic sample bends upward, and after the electric field is removed, the sample can maintain the bending deformation for a long time; when an electric field of 60 kV / cm is applied to the lower surface, the long ceramic sample bends downward, and after the electric field is removed, the sample can maintain the downward bending state for a long time, with a significant shape memory effect; when an AC electric field with an amplitude of 40 kV / cm and a frequency of 100 Hz is applied to the sample, the sample can quickly switch between bending upward and bending downward.

[0028] Embodiment 3: Select commonly used (Bi 0.5 Na 0.5 )TiO3 (coercive field is 56.3kV / cm), (K 0.5 Na 0.5 )O3 (coercive field is 8.51kV / cm), 0.7BiFeO3-0.3BaTiO3 (coercive field is 24.74kV / cm) and CaBi2Nb2O9 lead-free ferroelectric ceramics (coercive field is 94.74kV / cm) are taken as research objects, the thickness of the ceramic is about 1.5mm and the diameter is about 8mm: Step 1: First, use the heating platform to make the surface of the alumina sample block reach the temperature that melts the paraffin, then evenly apply the paraffin on the surface of the sample block where the sample will be fixed. After the sample block cools down, the ceramic sample will be fixed on the sample block. First, use a metallographic sample grinding and polishing machine with 500-grit sandpaper to thin the ceramic sample to a grinding depth of 0.3mm; then heat the sample block to separate the ceramic sample from the sample block, flip the sample, and continue to thin it after cooling, with a grinding depth of 0.3mm; alternate grinding in this way to thin the ceramic thickness to about 0.5mm; Step 2: Select 1000-grit sandpaper and use a metallographic sample grinding and polishing machine to continue grinding the piezoelectric ceramics so that the thickness of the ceramic samples of four different components reaches 0.12 mm; Step 3: Soak the polished thin slice sample in acetone to remove stains and paraffin on the sample surface. Then apply room temperature silver paste on the upper and lower surfaces of the sample and place it in an 80℃ oven to dry; Step 4: The frequency of the test voltage is fixed at 1Hz, and the test voltage amplitude starts from 100V and increases by 50V each time to the target voltage ((Bi 0.5 Na 0.5 )TiO3、(K 0.5 Na 0.5 )O3, 0.7BiFeO3-0.3BaTiO3 and CaBi2Nb2O9 were 1065V, 300V, 610V, 2100V respectively), and then the cycle test was performed 20 times at the target voltage, and finally stable ferroelectric strain performance was obtained.

[0029] like Figure 5 As shown, (Bi 0.5 Na 0.5 )TiO3, (K 0.5 Na 0.5 )O3, 0.7BiFeO3-0.3BaTiO3 and CaBi2Nb2O9 ceramics all exhibited a loop-shaped strain electric field curve when the thickness reached 0.12 mm, indicating the existence of shape memory effect. 0.5 Na 0.5 )TiO3, (K 0.5 Na 0.5 )O3 and 0.7BiFeO3-0.3BaTiO3 apparent strain output are both greater than ~3%, which greatly improves the strain output performance of single lead-free ferroelectric ceramic materials.

[0030] Example 4 The 0.1 mm thick ceramic sample 4 prepared in Example 1 was placed in the sample chamber of a ferroelectric analyzer, and the maximum electric field strength was set to 54 kV / cm (1.2 times the coercive field), the frequency was 1 Hz, the number of cycles was 20, and the residual polarization intensity was 11.95 μC / cm 2 , the apparent strain is 2.16%.

[0031] Example 5 The 0.1 mm thick ceramic sample 4 prepared in Example 1 was placed in the sample chamber of a ferroelectric analyzer, and the maximum electric field strength was set to 71.5 k / cm (1.6 times the coercive field), the frequency was 1 Hz, the number of cycles was 20, and the residual polarization intensity was 21.98 μC / cm 2 , the apparent strain is 6.87%.

[0032] Example 6 The 0.1 mm thick ceramic sample 4 prepared in Example 1 was placed in the sample chamber of a ferroelectric analyzer, and the maximum electric field strength was set to 84 kV / cm (2.04 times the coercive field), the frequency was 1 Hz, the number of cycles was 20, and the residual polarization intensity was 28.6 μC / cm 2 The maximum apparent strain is 5.01%, which is lower than that of Example 5.

[0033] Comparative Example 1 The 0.1 mm thick ceramic sample 4 prepared in Example 1 was placed in the sample chamber of a ferroelectric analyzer, and the maximum electric field strength was set to 35 kV / cm (0.8 times the coercive field), the frequency was 1 Hz, the number of cycles was 20, and the residual polarization intensity was 3.341 μC / cm 2 , the apparent strain is 0.05%.

[0034] Table 1:

Claims

1. A method for making a ferroelectric ceramic material have large displacement and shape memory effects, characterized in that: include: After electrodes are prepared on the upper and lower surfaces of the ferroelectric ceramic sheet, they are subjected to multiple positive and negative electric field periodic polarization treatments to achieve the improvement of displacement and shape memory effects. The thickness of the ferroelectric ceramic sheet is ≤0.2 mm.

2. The method according to claim 1, characterized in that The material of the ferroelectric ceramic sheet includes one of sodium bismuth titanate-based ferroelectric ceramics, sodium potassium niobate-based ferroelectric ceramics, sodium bismuth titanate-barium titanate solid solution system ferroelectric ceramics, bismuth ferrite-barium titanate solid solution system ferroelectric ceramics, bismuth tungstate ferroelectric ceramics and bismuth calcium niobate ferroelectric ceramics.

3. The method according to claim 1, characterized in that The method for thinning the ferroelectric ceramic sheet comprises: When the thickness of the ferroelectric ceramic sample is greater than 0.5 mm, use 200-500 mesh sandpaper for thinning; When the thickness of the ferroelectric ceramic sample is ≤0.5 mm, use 500-2000 mesh sandpaper for thinning.

4. The method according to claim 1, characterized in that: The electrode is a precious metal electrode, preferably a gold electrode, a platinum electrode or a silver electrode; the preparation method of the precious metal electrode comprises: applying a precious metal slurry on the upper and lower surfaces of a ferroelectric ceramic sheet, and then drying or further sintering to obtain a precious metal electrode; preferably, the sintering temperature is 550 to 850° C., and the time is 10 to 30 minutes.

5. The method according to claim 1, characterized in that The electric field intensity of the multiple positive and negative electric field periodic poling treatments is greater than the coercive field of the ferroelectric ceramic sheet, preferably 1.2 to 2.2 times the coercive field of the ferroelectric ceramic sheet, and more preferably 1.2 to 1.6 times the coercive field of the ferroelectric ceramic sheet; The frequency of the multiple positive and negative electric field periodic polarization treatments is 0.1 to 20 Hz; The number of cycles of the multiple positive and negative electric field periodic polarization treatments is at least 20.

6. The method according to claim 1, characterized in that The thickness of the ferroelectric ceramic sheet is 0.05-0.2 mm, preferably 0.1 mm.

7. A ferroelectric ceramic sheet prepared by the method according to any one of claims 1 to 6.